The Art of War: Ferroptosis and Pancreatic Cancer - Liu, Jiao; Kang, Rui; Tang, Daolin (Frontiers in Pharmacology, 2021)
Pancreatic cancer is a devastating gastrointestinal cancer, which is characterized by late diagnosis, low treatment success rate, and poor survival prognosis. The most common pathological type of pancreatic cancer is pancreatic ductal adenocarcinoma (PDAC), which is driven by the K-Ras oncogene. Ferroptosis was originally described as Ras-dependent cell death, but is now defined as lipid peroxidation-mediated regulated necrosis, accompanied by excessive activation of the autophagy degradation pathway and limited membrane repair capacity. The impaired ferroptotic pathway is involved in many types of cancer, including PDAC. On the one hand, the chronic inflammation caused by ferroptotic damage contributes to the formation of K-Ras-driven PDAC. On the other hand, drug-induced ferroptosis is an emerging strategy to suppress tumor growth in established PDAC. In this mini-review, we outline the core process of ferroptosis, discuss the regulatory mechanism of ferroptosis in PDAC, and highlight some of the challenges of targeting ferroptosis in PDAC therapy.